Perfluoroalkylsulfonyl ammonium for humidity- resistant printing high-performance phase-pure FAPbI3 perovskite solar cells and modules - Chen, Xining; Yang, Fu; Yuan, Linhao; Huang, Shihao; Gu, Hao; Wu, Xiaoxiao; Shen, Yunxiu; Chen, Yujin; Li, Ning; Egelhaaf, Hans-Joachim; Brabec, Christoph; Zhang, Rui; et al. (Joule, 2024)
High-quality phase-pure formamidinium lead triiodide (FAPbI3) perovskite film needs to be fabricated under strict control of the surrounding atmosphere, which becomes more rigorous when large-area FAPbI3 film is involved, leading to high-performance FAPbI3 perovskite solar cells and modules predominantly carried out in an inert gas-filled atmosphere. In this work, we propose a scalable printing strategy for the large-area high-quality phase-pure FAPbI3 film under a high-humidity atmosphere (up to 75% ± 5% relative humidity) by regulating the perovskite precursor ink with a functional perfluoroalkylsulfonyl quaternary ammonium iodide. This approach decreases the energy barriers of cubic phase formation and heterogeneous nucleation, thereby regulating the FAPbI3 crystallization. The printed photovoltaic small-area cells and large-area modules achieved remarkable power conversion efficiencies of 24.37% and 22.00%, respectively. Specifically, the unencapsulated device exhibits superior operational stability with T90 > 1,060 h, ambient stability with T90 > 2,020 h, and thermal stability with T90 > 2,350 h.
CRIS-Team Scopus Importer:2024-07-19
Keywords: blade coating; film formation; humid atmosphere; perovskite crystallization; perovskite solar cells; scalable printing; solar module; stable perovskite